Out‐of‐pocket expenditures in adult patients with prurigo nodularis in France - Laurent Misery; Christine Patras deCampaigno; Denis Jullien; Adrien Marquie; Sylvie Gabriel; Charles Taieb; Carle Paul (Wiley, 2023)
Abstract Background Chronic prurigo or prurigo nodularis is a severe condition with chronic pruritus and skin lesions. Current unnmet medical needs are numerous and generate a significant burden for the patients. Financial consequences are poorly known. Objectives The aim of this study was to evaluate out‐of‐pocket (OOP) expenditures for the patients. Methods A digital detailed questionnaire was submitted to adult patients living in France. The severity of pruritus was assessed with the 5‐D itch scale and the psychological well‐being was assessed with the well‐being questionnaire WBQ‐12. Results A total of 141 patients answered to all questions. The mean global score for the 5‐D itch scale was 16/25. The mean WBQ‐12 score was low: 14.7/36. The amount of OOP expenditures was high in patients with chronic prurigo (€855 ± 769 [median €605]). It was correlated with the severity of itch, higher in women than in men, higher when lesions were visible, and inversely correlated with psychological well‐being. Conclusions Chronic prurigo or prurigo nodularis is insufficiently managed and treated until now. Consequently, itch remains poorly treated, the psychological well‐being is deeply altered, and the personal cost related to the disease remains high for these patients.